Build Internet of Thing Based Sea Level Detection System - Rizalul Akram; Liza Fitria (Universitas Medan Area, 2021)
Tides can be defined as waves generated by the interaction between the earth, sun and moon. The peak of the wave is called the high tide (High Water/HW) and the tide is called low tide (Low Water/LW). The tidal period is the time between the crest or trough of a wave to the crest or tide of the next wave. The time of the tidal period varies from 12 hours 25 minutes to 24 hours 50 minutes. The results of preliminary observations to the desa nelayan in Kuala Langsa found that most of the outskirt fishermen and anglers always look for fish and other marine animals in high tide conditions. Nevertheless, they do not know for sure when the sea water will rise. They detect sea level rise using only a simple tool such as a stick attached to the river and from their house poles under the water. This condition can be detrimental to fishermen both time and economically. The author also began to think about how to create a detection tool that can provide accurate information on sea level conditions at any time to fishermen and anglers via smartphones. The author finally got the best idea, namely creating a